“Only fatness will bring rain”: agriculturist rainmaking and hunter-gatherers - Whitelaw, G. (Southern African Humanities, 2017)
Agriculturist rainmaking is significant in archaeological studies of interaction with hunter-gatherers. Scholars draw inspiration from the Mpondomise use of Bushman rainmakers in the nineteenth and early twentieth centuries, and apply this example to other contexts across space and time. The evidence shows that Mpondomise rainmaking was similar in principle to that of other Nguni speakers between the uPhongolo and Great Fish rivers, and indeed of all ranked societies in southern Africa. The Mpondomise use of Bushman specialists was, however, distinctive, and a logical consequence of a political appeal to autochthony. Their rainmaking work annually reinforced the autochthonous authority of the ruling line. This arrangement probably dates from the early to mid-1700s.